(untitled) (Citizenship in Action: Extension and Culture Magazine, 2023)
ABSTRACT Introduction: As one of the main Extension Actions of Santa Catarina State University (UDESC), the Rondon Extension Center – NER/UDESC enables the exchange of scholars in different branches of knowledge and the university’s involvement in different scenarios of the state of Santa Catarina and other states in Brazil. Objective: To provide a report on Rondon’s contribution in the educational process, a subtle approach based on a dialogue of discoveries over Paulo Freire’s theoretical framework. Results: Four Operations were experienced through the Rondon Extension Center – UDESC: three as an academic in the nursing program in the Midwest of Santa Catarina and one working alongside a colleague in the coordination of the Operation. Amid the diversity of the extension workers from the different centers of knowledge, we develop activities with different individuals, from children to teenagers to youth to adults to the elderly. Given the diversity of the community, it was necessary to adapt different approaches to schoolchildren, health professionals, education professionals, public servants, community leaders, people with special needs, people in institutionalized environments or hospitalized, people who live in hard-to-reach places, among others. It was necessary to integrate the different sectors of society, such as education, culture, health, human rights, justice, communication, technology, environment, labor, and production. Various issues were addressed based on the needs of the municipality and the knowledge offered by the academics in different disciplines. Rondon enables an approximation between the academy and society, an extension experience which all academics should have the opportunity to experience, as it brings us closer to what is real and (trans)forms us. Conclusion: I add to my baggage of learning experiences as a Rondonist the understanding that we must all be the “subjects of our own (trans)formation,” find meaning in what we are doing, and be involved with the reality of our communities, which is not stable. It moves and modifies.